An Analysis of Grammatical Metaphor Representation and Transgrammatical Semantic Domains in Narrative Text Entitled Three Fishes - Sianipar, Maria Olivia Christina (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2019)
This research is aimed to find out the easy way for students in Indonesia to understand and to translate English text to Bahasa Indonesia. In doing this research, the researcher uses a form of a detailed examination of one setting a single subject, a single depository of documents or one particular even which is stated by Bogdan & Biklen (1992:62) as a case study. However, the descriptive qualitative research as stated by Miles, Huberman and Saldana (2014) is applied in analyzing the data. Researcher realizes that Indonesian students are still very difficult to understand and translate the English texts as the texts are coded in grammatical metaphor. Although Indonesian students already get English lesson from grade school or at junior high school, but still they are difficult to understand and translate any kinds of English text. It is expected by applying transgrammatical semantic domains Indonesian students can understand the texts and can translate the English text into good Bahasa Indonesia. This narrative text entitled ‘Three Fishes’ which is a short interesting story that has a good lesson, that makes easy to understand about the topic of this research that is knowledge or competence of Grammatical Metaphor and Transgrammatical Semantic in Text which is written in English. This way Indonesian students will be more interesting to read the text because they can understand and translate the text into Bahasa Indonesia easier.